1994
DOI: 10.1104/pp.105.3.989
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Autonomous Cytokinin-Independent Growth of Tobacco Cells Transformed by Agrobacterium tumefaciens Strains Lacking the Cytokinin Biosynthesis Gene

Abstract: Mutations at the cytokinin biosynthesis locus (tmr) of Agrobacterium tumefaciens usually result in strains that induce tumors exhibiting the rooty phenotype associated with high auxin-tocytokinin ratios. However, tobacco (Nicotiana tabacum cv Havana 425) leaf disc explants responded to t m f mutant strain A356 by producing rapidly growing, unorganized tumors, indicating that these lines can grow in a cytokinin-independent fashion despite the absence of a functional tmr gene. Severa1 methods have been used to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…The concept is that certain hosts (or host tissues) infected with mutant bacterial strains activate physiological systems that overcome the absence of a T-DNA oncogene, resulting in tumors indistinguishable from those induced by wild type strains. A similar case was observed when N. tabacum leaf explants were transformed by an octopine type Agrobacterium strain mutated in the ipf gene but wild type for the iaaH and iaaM loci: the resultant transformants were cytokinin independent, even though leaf explants provided with exogenous auxin were cytokinin requiring (Black et al, 1994). When such tumors of N. glutinosa were put into tissue culture, they exhibited an auxin independent growth phenotype in the absence of shoot formation.…”
Section: Iila2 Complementation Of T-dna Oncogene Mutations By Hostmentioning
confidence: 56%
“…The concept is that certain hosts (or host tissues) infected with mutant bacterial strains activate physiological systems that overcome the absence of a T-DNA oncogene, resulting in tumors indistinguishable from those induced by wild type strains. A similar case was observed when N. tabacum leaf explants were transformed by an octopine type Agrobacterium strain mutated in the ipf gene but wild type for the iaaH and iaaM loci: the resultant transformants were cytokinin independent, even though leaf explants provided with exogenous auxin were cytokinin requiring (Black et al, 1994). When such tumors of N. glutinosa were put into tissue culture, they exhibited an auxin independent growth phenotype in the absence of shoot formation.…”
Section: Iila2 Complementation Of T-dna Oncogene Mutations By Hostmentioning
confidence: 56%
“…Tumorous lines obtained by transformation of Hl-1 with pTiT37 ipt − [31] do not accumulate elevated levels of cytokinins, suggesting that autonomous growth might be due to increased growth-factor sensitivity, or even the activation of growth-factor-independent pathways. A lack of correlation between cytokinin content and the A + C + phenotype has also been reported for tumorous lines obtained by transforming wild-type tobacco with another defective plasmid, pTiA6 ipt − [9]. In this case, the hormone-autotrophic lines contained elevated levels of dehydrodiconiferyl alcohol glucosides, which are known to promote cell division [44].…”
Section: Discussionmentioning
confidence: 85%
“…The uncontrolled synthesis of auxin and cytokinin by cells transformed with a T-DNA of tumorigenic Ti-plasmids drives tumor development, while the auxin to cytokinin ratios determine the crown gall morphology ( Figure 1B ). In the early days of studies about the molecular basis of crown gall development it was observed that mutations in the tmr locus encoding ipt cause rooty crown galls and those in the tms loci coding for iaaH and iaaM induce shooty phenotypes ( Garfinkel et al, 1981 ; Akiyoshi et al, 1983 ; Barry et al, 1984 ; Buchmann et al, 1985 ; Black et al, 1994 ). A recent study on the T-DNA locus Atu6002 of strain C58 indicated that when the encoding protein C is expressed, it increases host cell sensitivity to auxin ( Lacroix et al, 2013 ).…”
Section: Host Responses To Crown Gall Developmentmentioning
confidence: 99%